Use of Over-the-Counter Medication among Pregnant Women in Sharjah, United Arab Emirates - Abduelmula R. Abduelkarem; Hafsa Mustafa (Hindawi Limited, 2017)
Background. Over-the-counter medications are widely available in pharmacies Their safety profile, however, does not extend to pregnant women. Accordingly, there should be educational programs developed for pregnant women to protect them from the harms of the side effects. Aim. This study was planned and designed with the aim of exploring the awareness and assessing the usage of OTC medications among pregnant women in Sharjah, UAE. Method. A cross-sectional survey using a self-administered questionnaire. Results. More than three-quarters (75.7%) reported that they are familiar with the term "over-the-counter drugs." Interestingly, 40% of the respondents reported that they took OTC drugs during pregnancy, and the majority (94.2%) agreed with the survey statement "not all OTC medications are safe to be taken during pregnancy." Constipation was the most frequent side effect that most of the participants reported during the study period. Folic acid (36%), calcium (28.6%), and iron (35.1%) were the most common supplements used by the pregnant women responding. Conclusion. The reported 40% usage of OTC medications among pregnant women in this study is worrisome and calls for the need to educate, counsel, and increase awareness among pregnant women regarding the dangers of OTC drugs usage while pregnant in Sharjah, UAE.